2017
DOI: 10.1186/s12872-017-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of sleep disordered breathing with left ventricular remodeling in CAD patients: a cross-sectional study

Abstract: BackgroundThere is still insufficient knowledge on the potential effect of mild to moderate sleep-disordered breathing (SDB) that is widely prevalent, often asymptomatic, and largely undiagnosed in patients with stable coronary artery disease (CAD). SDB affects 34% of men and 17% of women aged between 30 and 70. The objective of this study was to evaluate the association between SDB and left ventricular (LV) hypertrophy as well as structural remodeling in stable CAD patients.MethodsThe study was based on a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…However, these parameters did not correlate with CAHI or OAHI. This finding contrasts the adult literature, where sleep disordered breathing is associated with left ventricular remodeling 20 . However, this is supported by previous studies in pediatric literature which suggest that pediatric sleep disordered breathing is not associated with significant cardiovascular strain and the majority of cardiovascular parameters in children with sleep disordered breathing are within the normal range at baseline 21 …”
Section: Discussioncontrasting
confidence: 60%
“…However, these parameters did not correlate with CAHI or OAHI. This finding contrasts the adult literature, where sleep disordered breathing is associated with left ventricular remodeling 20 . However, this is supported by previous studies in pediatric literature which suggest that pediatric sleep disordered breathing is not associated with significant cardiovascular strain and the majority of cardiovascular parameters in children with sleep disordered breathing are within the normal range at baseline 21 …”
Section: Discussioncontrasting
confidence: 60%
“…In contrast to these studies, we found that the presence of concentric hypertrophy in IgAN patients was the worst prognostic LV geometry in both sexes. Other studies found concentric hypertrophy the most common LV geometry alteration and the worst in terms of progression in general, in the case of hypertension, obesity, sleep apnea syndrome, and CV disease [ 34 , 35 ]. Our data suggest that, like in other diseases, concentric hypertrophy is the worst prognosis in IgAN (and possibly in other CKDs).…”
Section: Discussionmentioning
confidence: 99%
“…Parameters of left ventricular hypertrophy, including left ventricular mass/height relationship, wall thickness criteria and concentric left ventricular hypertrophy, were all higher in OSA. Even mild OSA independently predicted left ventricular hypertrophy after multiple logistic regression [61].…”
Section: Prognostic Relevance Of Osa In Acs/amimentioning
confidence: 97%
“…Structural changes of the myocardium may influence the long-term outcome of patients with OSA and CAD. ALONDERIS et al [61] investigated the impact of SDB on left ventricular hypertrophy in stable CAD patients. They performed a cross-sectional study in 772 patients with CAD and untreated OSA.…”
Section: Prognostic Relevance Of Osa In Acs/amimentioning
confidence: 99%